2019
DOI: 10.1108/emjb-04-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

The influence of strategic alliances on human capital development

Abstract: Purpose The purpose of this paper is to analyse the influence of strategic alliances (knowledge/learning, efficiency and market motives) on the development of human capital. Design/methodology/approach To do so, a quantitative study was chosen, with data on technology-based small and medium-sized enterprises (SMEs) in Portugal, leading to 257 valid answers. Findings The results obtained from a structural equation model show that motives for strategic alliances (knowledge/learning, efficiency and market) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 87 publications
0
35
0
Order By: Relevance
“…Developed human capital is strategically important and valuable to the firm. Improving human capital can be achieved through one-to-one training, organizing training events, training and skills development to encourage the exchange of knowledge, experience and know-how between employees and customers (Muda & Rahman, 2016;Ferreira & Franco, 2019). It is noted that there is a relationship between the influence of human capital on the success of the firm and how the knowledge of managers/owners of SMEs was obtained.…”
Section: Human Capital In Smes Management or Service Sectormentioning
confidence: 99%
“…Developed human capital is strategically important and valuable to the firm. Improving human capital can be achieved through one-to-one training, organizing training events, training and skills development to encourage the exchange of knowledge, experience and know-how between employees and customers (Muda & Rahman, 2016;Ferreira & Franco, 2019). It is noted that there is a relationship between the influence of human capital on the success of the firm and how the knowledge of managers/owners of SMEs was obtained.…”
Section: Human Capital In Smes Management or Service Sectormentioning
confidence: 99%
“…However, in the context of product and process open innovation, the firms must possess the abilities to structure, consolidate and reconstitute their sources (Li and Liu, 2014; Santoro et al , 2019). Hence, companies functioning in different countries as subsidiaries of multinational firms must possess such capabilities to best utilize the open innovation through marketing knowledge management (Ferreira and Franco, 2019; Kang and Kang, 2014; Sreenivasulu, and Chatterjee, 2019). To survive in the international market through marketing knowledge management (MKM), the subsidiaries must benefit from the potentials of open innovation by improving their dynamic capabilities (Teece et al , 1997; Hill and Rothaermel, 2003) and sensing activities by seizing the observed opportunities (Cepeda and Vera, 2007; Inoue and Liu, 2015; Kizgin et al , 2019), and by appropriately reconfiguring their abilities (Ferreira and Franco, 2019; Kar and Chatterjee, 2019; Wu, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, companies functioning in different countries as subsidiaries of multinational firms must possess such capabilities to best utilize the open innovation through marketing knowledge management (Ferreira and Franco, 2019; Kang and Kang, 2014; Sreenivasulu, and Chatterjee, 2019). To survive in the international market through marketing knowledge management (MKM), the subsidiaries must benefit from the potentials of open innovation by improving their dynamic capabilities (Teece et al , 1997; Hill and Rothaermel, 2003) and sensing activities by seizing the observed opportunities (Cepeda and Vera, 2007; Inoue and Liu, 2015; Kizgin et al , 2019), and by appropriately reconfiguring their abilities (Ferreira and Franco, 2019; Kar and Chatterjee, 2019; Wu, 2010). To internationalize the knowledge management process to improve marketing abilities, multinational firms must take appropriate steps so that their subsidiaries develop the abilities to reconstruct, integrate, create, renovate and, in some cases, dispose the existing resources for product and process innovation (Becker and Dietz, 2004; Teece, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…SME's distribute capital to maintain risk and cost related variables in order to increase sustainable activities (Srisathan et al, 2020). They are able to achieve significant growth, competitive performance, and an enduring reputation for their businesses (Ferreira & Franco, 2019). Employees that are active in delivering effective services contribute to the success of a small business.…”
Section: Introductionmentioning
confidence: 99%